LITERATURE STUDY: THE INFLUENCE OF SUCCESS DEEP WORK TEAM DEVELOPMENT INTERVENTION ORGANIZATIONAL DEVELOPMENT - Andini, Tiara Dea; Magriasti, Lince Magriasti (Jurnal Ekonomi Manajemen, 2023)
In the process of organizational development, every aspect undergoes changes both from within and from outside the organizational environment. To balance these changes, an organization makes the necessary interventions. One intervention that focuses on Human Resources is the Work Team Development Intervention. It is explained that teamwork and organizational members are the backbone of an organization. Without good cooperation or teamwork, an organization will not be ready to face change, let alone develop. Work team development is carried out by a leader, and carried out by organizational members who are part of the organization. To be able to produce good teamwork, organizational members must be able to interact and communicate well with each other, between groups, and with superiors. Good interaction produces good social relations in the organization, with this good relationship an organizational group can unite their voices and thoughts to jointly achieve organizational goals more efficiently and satisfactorily. This research was conducted using qualitative research methods with a descriptive approach, then data collection techniques using literature studies to find the effect of the success of the Work Team Coaching Intervention in an effort to develop the organization.